Diffusion of agricultural innovations in Guinea-Bissau: From learning to doing - Rute Martins Caeiro (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper analyses the pathways of technology diffusion through social networks, following the experimental introduction of new technologies in Guinea-Bissau. In the context of an agricultural extension project, we document both the direct effects of this intervention and subsequent diffusion from trainees to the wider community. In order to test for social learning, we exploit a detailed census of households and social connections across different social dimensions. In our first result, we show that trainees' knowledge and adoption rose immediately after training, remaining stable thereafter. Secondly, we show that agricultural information diffuses along social network links from project participants to non-participants. However, these effects are heterogeneous across different types of networks-the most relevant being a farmer's 'financial support'. Despite positive effects in knowledge, evidence of network impacts on actual adoption behaviour is more limited.
Keywords: O13; O31; Q16; 330; agriculture; technology adoption; social learning; social networks